Administrative Law and Equity in Higher Education: Lessons from the Arab Region - Almutairi, Maryam (Journal of Legal Sciences, 2026)
The right to higher education is an essential component of human rights and crucial for personal and societal development. In the current field of education, diversity, inclusion, and equity have become essential components. The purpose of this research was to examine the role of administrative law in promoting equity in higher education across the Arab region.A qualitative, descriptive design using document analysis was used. Data from government reports, academic studies, and international organization were synthesized. the results indicated that several Arab countries have implemented different reforms aimed at increasing inclusivity and equity of women in education and economic activities, evident in inclusion in their notable inclusion leadership roles, participation in economic activities, and increase access to higher education. In addition, several Arab countries have streamlined the student visa application procedures, leading to notable increase in international students across different Arab universities. Different administrative law frameworks, such diversity quotas, simplified legal procedures, and oversight bodies have significant potentials in enhancing inclusivity and equity in higher learning institutions. Based on the research results recommended to ensure administrative laws contribute to equitable education systems. These findings provide valuable insights for global higher education policymakers.